Molecular Mechanism Analysis of Intensive LightInduced Retinal Damages: Light-induced retinal damages - Rostami Nejad, Mohammad; Razzaghi, Zahra; M Robati, Reza; Arjmand, Babak; Rezaei-Tavirani, Mostafa; Hamzehloo-Moghadam, Maryam; Keramatinia, Aliasghar (Journal of Lasers in Medical Sciences, 2024)
Introduction: The retina is a light-sensitive tissue, and intensive light exposure leads to lightinduced retinal damage. It is pointed out that photoreceptor damage is responsible for the decrease in retina function. The aim of this study was to detect the main genes and biological terms which are involved in retinal response to intensive light exposure. Methods: The effect of intensive light on the mouse retina function was searched in the Gene Expression Omnibus (GEO) database. The data of GSE22818 were assessed by the GEO2R program. The significant differentially expressed genes (DEGs) were determined and evaluated via directed protein-protein interaction (PPI) network analysis. The critical significant DEGs were enriched via gene ontology analysis to find the related biological processes, molecular function, and biochemical pathways. Results: Data analysis indicates that the high intensity of light induces gene expression alteration in the retina. 105 significant DEGs were identified as the main responsive genes to light damage in the retina. STAT3, JUN, IL6ST, SOCS3, ATF3, JUNB, FOSL1, CCL2, ICAM1, FGF2, AGT, MYC, LIF, CISH, and EGR1 were introduced as the critical affected genes. STAT3, JUN, IL6ST, SOCS3, and ATF3 and “Positive regulation of the receptor signaling pathway via JAK-STAT” were highlighted as the key elements of molecular events. Conclusion: It can be concluded that regulation of the key DEGs and the dependent biological terms can effectively provide tools to prevent the development of light-induced retinal damage.